Tradisi Nikah Payung Sekaki (Studi Living Hadits di Desa Muara Madras Kecamatan Jangkat, Jambi) - Syahidil Mubarik Mh (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Abstract Jambi Malays have diverse traditions, such as the Payung Sekaki marriage tradition in the village of Muara Madas, Jambi. The purpose of this research is to find out the hadith foundation behind the Payung Sekaki marriage tradition. As for data collection techniques using observation, interviews, and documentation. The data analysis process in this study uses Peter L. Berger's sociology of knowledge theory. The results of this study indicate that the practice of the Payung Sekaki marriage tradition in the village of Muara Madras is the practice of the Hadith helping each other which originates from the traditional motto